2005
DOI: 10.1557/proc-0892-ff13-04
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Current Leakage in Ni Schottky Diodes on Cubic GaN and AlxGa1-xN Epilayers

Abstract: Ni Schottky-diodes (SDs) 300 μm in diameter were fabricated by thermal evaporation using contact lithography on cubic GaN and AlxGa1-xN epilayers. Phase-pure cubic GaN and c-Al0.3Ga0.7N/GaN structures were grown by plasma assisted molecular beam epitaxy (MBE) on 200 µm thick free-standing 3C-SiC (100) substrates. The quality of the cubic group III-nitride epilayers was checked by high resolution X-ray diffractometry, atomic force microscopy and photoluminescence at room temperature and at 2 K. Large deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…24,25) The generation mechanism of gate current has been extensively investigated by Hashizume and coworkers. [26][27][28][29][30][31] These authors suggested a thin surface barrier (TSB) model to explain gate current. In this model, the potential profile of the Schottky barrier near the metal-semiconductor interface is modified owing to the existence of a high-density positive fixed charge for donor-type deep surface states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25) The generation mechanism of gate current has been extensively investigated by Hashizume and coworkers. [26][27][28][29][30][31] These authors suggested a thin surface barrier (TSB) model to explain gate current. In this model, the potential profile of the Schottky barrier near the metal-semiconductor interface is modified owing to the existence of a high-density positive fixed charge for donor-type deep surface states.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous gate current studies by Hashizume and coworkers 28,30) and As et al 29) were performed using Schottky junction diode samples. Furthermore, in the case of using a transistor (HEMT), these studies were performed under an off-state bias condition.…”
Section: Introductionmentioning
confidence: 99%